(untitled) (Bioagro, 2020)
The foothills of the Llanos Orientales of Colombia are characterized by having small- and medium-scale citrus producers, who perform agronomic management practices that require adjustments to increase the productivity. The aim of this study was to diagnose the nutritional status of ’Valencia’ orange (Citrus sinensis [L.] Osbeck) and ’Arrayana’ mandarin (Citrus reticulata Blanco) on farms in the foothills of the Department of Meta, as a baseline for future experiments to establish nutritional requirements for these crops. Leaf samples were taken in 19 plots cultivated with orange and 18 with mandarin located in four municipalities with three soil classes (Classes II and III Inceptisols, and Class IV Oxisols). Foliar concentrations of N, P, K, Ca, Mg, Zn, B, Fe, Cu, and Mn were measured and compared with reference levels found in the literature, as well as with productivity values. Results showed that for both crops all the samples had Ca and Zn deficiencies, between 50 and 70 % of these had N, P, K, Mg, and Mn deficiencies in orange, meanwhile, in mandarin, in addition to Ca and Zn, Mg deficiencies were found in about 55 % of the samples. This indicates that in the studied area, Ca is a limiting nutrient for citrus nutrition followed by Zn and Mg. Further, the kind of soil had effects on productivity of both crops, being higher in the trees established in the Inceptisols-Class II soils.